1987
DOI: 10.1139/b87-159
|View full text |Cite
|
Sign up to set email alerts
|

Fungi associated with halophytes of an inland salt marsh, Manitoba, Canada

Abstract: Six halophytic plants including Atriplex patula, Glaux maritima, Hordeum jubatum, Puccinellia nuttalliana, Salicornia rubra, and Suaeda depressa were collected at various growth stages throughout the growing season of the summers 1982 and 1983 from an inland salt marsh at Delta, Man. Washed root and shoot pieces of each plant species were plated on culture medium, incubated, and surveyed for cauloplane and rhizoplane fungi. A total of 31 taxa were isolated including 3 asco-mycetes, 2 coelomycetes, 1 zygomycete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The dominance of Alternaria sp. (Ascomycota) in S. europaea was previously reported in Canada (Muhsin and Booth 1987), Japan (Okane and Nakagiri 2015), South Korea (You et al 2014) and India (Kannan et al 2014). However, Alternaria may not be a dominating species in all halophytes: a few examples include Artemisia fukudo, Carex scabrifolia, Kochia scoparia, Phragmites communis, Suaeda australis and S. japonica found in the Suncheon bay in South Korea (Young-Hyun et al 2012); Acanthus ilicifolius, Arthrocnemum indicum, Suaeda maritima and Sesuvium portulacastrum from mangroves in India (Suryanarayan and Kumaresan 2000); and S. maritima, Limonium tetragonum, Suaeda australis, Phragmites australis, and Suaeda glauca from Muan salt marsh of South Korea (Khalmuratova et al 2015).…”
Section: Culturable Diversity Of Endophytic Fungi In S Europaeamentioning
confidence: 70%
“…The dominance of Alternaria sp. (Ascomycota) in S. europaea was previously reported in Canada (Muhsin and Booth 1987), Japan (Okane and Nakagiri 2015), South Korea (You et al 2014) and India (Kannan et al 2014). However, Alternaria may not be a dominating species in all halophytes: a few examples include Artemisia fukudo, Carex scabrifolia, Kochia scoparia, Phragmites communis, Suaeda australis and S. japonica found in the Suncheon bay in South Korea (Young-Hyun et al 2012); Acanthus ilicifolius, Arthrocnemum indicum, Suaeda maritima and Sesuvium portulacastrum from mangroves in India (Suryanarayan and Kumaresan 2000); and S. maritima, Limonium tetragonum, Suaeda australis, Phragmites australis, and Suaeda glauca from Muan salt marsh of South Korea (Khalmuratova et al 2015).…”
Section: Culturable Diversity Of Endophytic Fungi In S Europaeamentioning
confidence: 70%
“…eichhorniae predominated the endophyte assemblages and preferred to colonize the stems rather than the roots. Alternaria fungi as dominant endophytes showing preference in specific tissues but very low specificity with respect to host species, were mainly isolated from leaves in six halophytes in inland salt marsh of Canada (Muhsin and Booth 1987), in eight halophytes in Tennger Desert of China (Sun et al 2012b), and in eight gypsophilous flowering plants in New Mexico desert (Porras-Alfaro et al 2014). These previous studies in halophytes and desert gypsophytes indicated that some endophytic fungi show strong tissue preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Ellis (1976) described pegs on the conidiogenous cells but these may be confused with extensions from the conidia as seen in SEM micrographs. D. arenaria is frequently reported from saline environments (Kohlmeyer and Kohlmeyer, 1979) and it is known from various saltmarsh halophytes (Gessner and Goos, 1973b;Kohlmeyer and Kohlmeyer, 1979;Muhsin and Booth, 1987). Our collection represents the first report of the species from Iraq.…”
Section: Cumulospora Marina Imentioning
confidence: 85%
“…2010. The fungus was reported on the aerial parts of Spartina alterniflora (Gessner, 1977) and halophytic plants from an inland salt marsh at Delta, Man, Manitoba, Canada (Muhsin and Booth, 1987). The species has been described as Drechslera halodes on dead culms of Cyperus rotundus submerged in Shatt Al-Arab River near Al-Khora tributary, Basrah, southern Iraq (Abdulkadir and Muhsin, 1991).…”
Section: Cumulospora Marina Imentioning
confidence: 99%
See 1 more Smart Citation